Peran Pelatihan Konvensional dalam Pengembangan Organisasi dan Dunia Industri - Arman Maulana (Coopetition : Jurnal Ilmiah Manajemen, 2023)
Training and development is a field related to organizational activities aimed at improving individual and group performance in an organizational environment. As a joint role commonly known as human resource development (HRM), namely developing human resources to remain competitive. Training focuses on taking actions to develop employees for their current jobs and development that prepares employees to take on future roles and responsibilities. It makes the analysis that the goal of training and development is for innovative learning organizations to ensure that employees, through added value, are able to do their job effectively, get results, gain competitive advantage and seek personal growth. Measurable performance due to good training and development will increase organizational growth. This process is called transferring information and knowledge to the employer. This enables employers to put this information and knowledge into practice with the aim of increasing organizational efficiency and growth, and the quality of human resource management should be considered alongside educational policies and systems so important to human capital development.